Genome-wide association study of multiple congenital heart disease phenotypes identifies a susceptibility locus for atrial septal defect at chromosome 4p16 - Cordell, H; Bentham, J; Topf, A; Zelenika, D; Heath, S; Mamasoula, C; Cosgrove, C; Blue, G; Granados-Riveron, J; Setchfield, K; Thornborough, C; Breckpot, J; et al. (2013)
We carried out a genome-wide association study (GWAS) of congenital heart disease (CHD). Our discovery cohort comprised 1,995 CHD cases and 5,159 controls and included affected individuals from each of the 3 major clinical CHD categories (with septal, obstructive and cyanotic defects). When all CHD phenotypes were considered together, no region achieved genome-wide significant association. However, a region on chromosome 4p16, adjacent to the MSX1 and STX18 genes, was associated (P = 9.5 × 10 -7) with the risk of ostium secundum atrial septal defect (ASD) in the discovery cohort (N = 340 cases), and this association was replicated in a further 417 ASD cases and 2,520 controls (replication P = 5.0 × 10 -5; odds ratio (OR) in replication cohort = 1.40, 95% confidence interval (CI) = 1.19-1.65; combined P = 2.6 × 10 -10). Genotype accounted for ∼9% of the population-attributable risk of ASD. © 2013 Nature America, Inc. All rights reserved.